2020
DOI: 10.1021/acs.orglett.0c01874
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot, Tandem Wittig Hydrogenation: Formal C(sp3)–C(sp3) Bond Formation with Extensive Scope

Abstract: A one-pot, tandem Wittig hydrogenation of aldehydes with stabilized ylides is reported, representing a formal C(sp 3 )−C(sp 3 ) bond construction. The tandem reaction operates under mild conditions, is high yielding, and is broad in scope. Chemoselectivity for olefin reduction is observed, and the methodology is demonstrated in the synthesis of lapatinib analogues and a formal synthesis of (±)-cuspareine. Early insights suggest that the chemoselectivity observed in the reduction step is due to partial poisonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In previous work, we found that concomitant reduction of the chromone C=C double bond resulted in depressed yields of the fully unsaturated hydrogenation product under similar reaction conditions, using Pd/C as a catalyst. 38 This was not observed in the preparation of chromone 15.…”
Section: Substrate Scope and Synthetic Applicationsmentioning
confidence: 90%
“…In previous work, we found that concomitant reduction of the chromone C=C double bond resulted in depressed yields of the fully unsaturated hydrogenation product under similar reaction conditions, using Pd/C as a catalyst. 38 This was not observed in the preparation of chromone 15.…”
Section: Substrate Scope and Synthetic Applicationsmentioning
confidence: 90%
“…For that, intermediate 13 was synthesized from salicylaldehyde (9) starting with a one-pot tandem Wittig reaction/ hydrogenation protocol employing a catalytic amount of N,Ndimethylacetamide (DMA) in aqueous ethanol to afford tertbutyl ester 10 in 86% yield (Scheme 2). 24 S N 2 reaction of 10 with 3-bromopropanol afforded 11 in 62% yield, which was followed by a Mitsunobu reaction employing diisopropyl azodicarboxylate (DIAD), triphenyl phosphine (PPh 3 ), and 5hydroxypyrimidine 12 (prepared via demethylation of commercially available 5 with BBr 3 in 90% yield) 25 and alcohol 11 to give 13 in 86% yield. Important to notice, attempts to submit 12 to S N 2 reactions led to starting material decomposition (see SI, Table S2).…”
mentioning
confidence: 99%